\(2=\frac{1954.0,24+76.19,54}{977.\left(x-4\right)}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

5 tháng 2 2018

\(\left(1+\frac{1}{2}\right)\times\left(1+\frac{1}{3}\right)\times\left(1+\frac{1}{4}\right)\times....\times\left(1+\frac{1}{98}\right)\times\left(1+\frac{1}{99}\right)\)

\(=\frac{3}{2}\times\frac{4}{3}\times\frac{5}{4}\times....\times\frac{99}{98}\times\frac{100}{99}\)

\(=\frac{3\times4\times5\times...\times99\times100}{2\times3\times4\times....\times98\times99}\)

\(=\frac{100}{2}=50\)

5 tháng 2 2018

(1+1/2).(1+1/3).(1+1/4)....(1+1/98).(1+1/99)

=3/2.4/3.5/4...99/98.100/99

=3.4.5....99.100/2.3.4....98.99

=100/2

=50

21 tháng 6 2018

a)13x3x32,27+67,63x39

=39x32,27+67,63x39

=39x(32,27+67,63)

=39x100

=3900

21 tháng 6 2018

b,= 1- [ 1/2 x 1/3 x1/4 x..... x 1/100 ]

=1/2 x 2/3 x 3/4 x .......x 99/100

= 1x2x3x......x99 / 2x3x4x...... x100 [ rút gọn ]

= 1/100

27 tháng 2 2020

= 1 nhé mk nhầm

27 tháng 2 2020

\(\left(x+\frac{1}{2}\right)+\left(x+\frac{1}{4}\right)+\left(x+\frac{1}{8}\right)+\left(x+\frac{1}{16}\right)=1\)

\(\Rightarrow\left(x+x+x+x\right)+\left(\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}\right)=1\)

\(\Rightarrow4x+\frac{15}{16}=1\)

\(\Rightarrow4x=\frac{1}{16}\)

\(\Rightarrow x=\frac{1}{64}\)

20 tháng 7 2019

a. \(\frac{-3}{2}-2x+\frac{3}{4}=-22\)2

=> \(-2x=-22+\frac{3}{2}-\frac{3}{4}\)

=> \(-2x=\frac{-85}{4}\)

=> \(x=\frac{-85}{4}:\left(-2\right)\)

=> \(x=\frac{85}{8}\)

b. \(\left(\frac{-2}{3}x-\frac{3}{5}\right).\left(\frac{3}{-2}-\frac{10}{3}\right)=\frac{2}{5}\)

=> \(\left(\frac{-2}{3}x-\frac{3}{5}\right).\frac{-29}{6}=\frac{2}{5}\)

=> \(\frac{-2}{3}x-\frac{3}{5}=\frac{2}{5}:\left(\frac{-29}{6}\right)\)

=> \(\frac{-2}{3}x-\frac{3}{5}=\frac{-12}{145}\)

=> \(\frac{-2}{3}x=\frac{-12}{145}+\frac{3}{5}\)

=> \(\frac{-2}{3}x=\frac{15}{29}\)

=> x = \(\frac{15}{29}:\frac{-2}{3}\)

=> x = \(\frac{-45}{58}\)

13 tháng 7 2018

a) (1,5 . 1,9 - x - 0,5) : 0,25 = 7,5 : 0,125

=> (2,85 - x - 0,5) : 0,25 = 60

=> (2,85 - 0,5) - x = 60 . 0,25

=> 2,35 - x = 15

=> x = 2,35 - 15

=> x = -12,65

Vậy x = -12,65

b) \(1-\left(5\frac{2}{9}+x-7\frac{7}{18}\right)\div2\frac{1}{6}=0\)

\(\Rightarrow\left(5\frac{2}{9}-7\frac{7}{18}+x\right)\div2\frac{1}{6}=1-0\)

\(\Rightarrow\left(\frac{47}{9}-\frac{133}{18}+x\right)\div2\frac{1}{6}=1\)

\(\Rightarrow\frac{-13}{6}+x=2\frac{1}{6}\)

\(\Rightarrow x=2\frac{1}{6}-\frac{-13}{6}\)

\(\Rightarrow x=\frac{13}{6}+\frac{13}{6}\)

\(\Rightarrow x=\frac{26}{6}\)

\(\Rightarrow x=\frac{13}{3}\)

Vậy \(x=\frac{13}{3}\)

c) \(35\left(2\frac{1}{5}-x\right)=32\)

\(\Rightarrow2\frac{1}{5}-x=32\div35\)

\(\Rightarrow\frac{11}{5}-x=\frac{32}{35}\)

\(\Rightarrow x=\frac{11}{5}-\frac{32}{35}\)

\(\Rightarrow x=\frac{9}{7}\)

Vậy \(x=\frac{9}{7}\)

d) \(\frac{4}{3}+\left(x\div2\frac{2}{3}-0,5\right).1\frac{35}{55}=0,6\)

\(\Rightarrow\left(x\div\frac{8}{3}-\frac{1}{2}\right).\frac{18}{11}=\frac{3}{5}-\frac{4}{3}\)

\(\Rightarrow\left(x\div\frac{8}{3}-\frac{1}{2}\right).\frac{18}{11}=\frac{-11}{15}\)

\(\Rightarrow x\div\frac{8}{3}-\frac{1}{2}=\frac{-11}{15}\div\frac{18}{11}\)

\(\Rightarrow x\div\frac{8}{3}-\frac{1}{2}=\frac{-121}{270}\)

\(\Rightarrow x\div\frac{8}{3}=\frac{-121}{270}+\frac{1}{2}\)

\(\Rightarrow x\div\frac{8}{3}=\frac{7}{135}\)

\(\Rightarrow x=\frac{7}{135}.\frac{8}{3}\)

\(\Rightarrow x=\frac{56}{405}\)

Vậy \(x=\frac{56}{405}\)

e) \(1\frac{1}{3}.2\frac{2}{4}\div\frac{5}{6}.1\frac{1}{11}=11-5\div x\)

\(\Rightarrow\frac{4}{3}.\frac{5}{2}\div\frac{5}{6}.\frac{12}{11}=11-5\div x\)

\(\Rightarrow\frac{10}{3}\div\frac{5}{6}.\frac{12}{11}=11-5\div x\)

\(\Rightarrow4.\frac{12}{11}=11-5\div x\)

\(\Rightarrow11-5\div x=\frac{48}{11}\)

\(\Rightarrow5\div x=11-\frac{48}{11}\)

\(\Rightarrow5\div x=\frac{73}{11}\)

\(\Rightarrow x=5\div\frac{73}{11}\)

\(\Rightarrow x=\frac{55}{73}\)

Vậy \(x=\frac{55}{73}\)

a) (1,5 * 1,9 - x - 0,5) : 0,25 = 7,5 : 0,125

(2,85 - x - 0,5) : 0,25 = 60

(2,85 - x - 0,5) = 60 x 0,25

(2,85 - x - 0,5) = 15

2,35 - x = 15

x = 2,35 - 15

x = -12,65

1 tháng 7 2017

2/ 

a) \(\frac{4}{1\cdot5}+\frac{4}{5\cdot9}+\frac{4}{9\cdot13}+\frac{4}{13\cdot17}+\frac{4}{17\cdot21}\)

\(=\left(1-\frac{1}{5}+\frac{1}{5}-\frac{1}{9}+....+\frac{1}{17}-\frac{1}{21}\right)\)

\(=1-\frac{1}{21}=\frac{20}{21}\)

b) \(\left(1-\frac{1}{2}\right)\cdot\left(1-\frac{1}{3}\right)\cdot\left(1-\frac{1}{4}\right)\cdot...\cdot\left(1-\frac{1}{2017}\right)\)

\(=\frac{1}{2}\cdot\frac{2}{3}\cdot\frac{3}{4}\cdot..\cdot\frac{2016}{2017}\)

\(=\frac{1}{2017}\)

c) \(A=2000-5-5-5-..-5\)(có 200 số 5) 

\(A=2000-\left(5\cdot200\right)\)

\(A=2000-1000\)

\(A=1000\)